Legal Protection for Consumers in Online Buying and Selling Transactions in Indonesia - Anggia Faradina (PT. Anagata Sembagi Education, 2024)
The development of information technology has driven the transformation of the trading system, including the rise of online buying and selling transactions. This phenomenon has given rise to various legal issues, especially related to consumer protection. This article aims to analyze the forms of legal protection available to consumers in online transactions in Indonesia and the effectiveness of its implementation. Using the normative legal method, this study examines relevant laws and regulations, such as the Consumer Protection Law (Law No. 8 of 1999), as well as other positive laws governing electronic transactions. The results of the study indicate that although legal instruments are available, their implementation still faces challenges, such as low consumer awareness of their rights and lack of law enforcement against online business actors who violate.